[Government House, Trinidad] - Norton, Noel (Ace Printery, Trinidad, 2009)
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Tropical Flora of the Botanical Gardens partially block the front of the Government House, Colonial style building and the home of the President.
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Gardens--Trinidad and Tobago; President's House, The